Developmental Structural Tooth Defects in Dogs – Experience From Veterinary Dental Referral Practice and Review of the Literature - Boy, Sonja; Crossley, David; Steenkamp, Gerhard (Frontiers in Veterinary Science, 2016)
Developmental tooth abnormalities in dogs are uncommon in general veterinary practice but understanding thereof is important for optimal management in order to maintain gnathic function through conservation of the dentition. The purpose of this review is to discuss abnormalities of enamel structure and macroscopic tooth anatomy in dogs encountered in veterinary dental referral practice in South Africa and the United Kingdom. The basis of the pathogenesis, resultant clinical appearance and the management principles of each anomaly will be considered. Future research should aim to provide a detailed individual tooth mineralization schedule for dogs.